(untitled) (Al-Academy, 2019)
The study aimed to study the role of technology in the production of the mural photography, and to develop its concept to the viewer, through the achievement of the aesthetic and functional vision. Through this study, some types of these techniques, which are organically related to architecture, were identified. The mural photography includes a huge amount of techniques, and methods, and the researcher presented them through five techniques: (AlTamira, Alfresk, acrylic, mosaic, and glass art, which takes the architectural character. The research consists of: Methodological framework: research problem, research objectives, research limits, importance of research, and definition of terms. Theoretical framework: The first section: techniques and mechanisms of construction in the mural art that has been distinguished through the ages. The second section: techniques used in the mural photography. Techniques in mural photography are multiple in implementation, where we find some of which is competent in accepted ways methods, and others related to the surface of the wall or the surface to add the mural painting for the architectural form. The procedural framework includes: research community - samples analysis - research methodology and then the researcher reached a number of results: The study aimed to develop the concept of the mural painting of the viewer, starting from the originality of thought and based on plastic principles and aesthetic values with high content, taking into account the element of raw materials and techniques that develop the traditional concept of mural photography art for the artist and the recipient, in addition to supporting and reviving the idea of organic link of the mural painting with architecture, on the one hand, and the interior design, on the other hand. The mural artists benefited from the materials, techniques, environmental and social conditions surrounding them and designed different methods and treatments depending on the environment and time period and then followed by proposals and recommendations